Transforming Industrial Downstreaming in Indonesia: Strengthening Value Creation within a Circular Economy Framework – A Literature Review - Tri Bayu Pamuji; Agus Suroso (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Industrial downstreaming has become a strategic policy adopted by many resource-rich countries to increase value creation and strengthen industrial competitiveness. Countries that rely heavily on exporting raw materials often capture only a limited portion of economic value within global production networks. Therefore, downstream industrialization is considered an important strategy for transforming resource-based economies into value-added industrial economies. This study aims to analyze the role of industrial downstreaming in strengthening value creation and supporting the transition toward a circular economy framework. This research employs a qualitative approach using a literature-based analytical method supported by thematic analysis and the Miles and Huberman model. Data were collected from academic journals, policy reports, and institutional publications related to industrial development, value chain upgrading, and circular economy practices. The analysis focuses on identifying key themes that explain the relationship between industrial downstreaming, value creation, competitive advantage, and sustainable industrial transformation. The findings indicate that industrial downstreaming significantly contributes to expanding domestic value chains, strengthening industrial competitiveness, and increasing economic value creation. Furthermore, the integration of circular economy principles into downstream industries improves resource efficiency and reduces environmental impact. However, successful implementation requires strong industrial policies, technological capability, and integrated industrial ecosystems.